Simultaneous Onset of Herpes Zoster Ophthalmicus and Chickenpox in the Context of Maternal Varicella; A Rare Case Report - Ali Alkarawi (Kirkuk Journal of Medical Sciences)
Varicella-zoster virus (VZV) is transmitted through airborne respiratory secretions, initially causing chickenpox. After the primary infection, the virus establishes latency within the dorsal sensory ganglia and may later reactivate, resulting in a vesicular dermatomal eruption known as herpes zoster (HZ). The simultaneous occurrence of herpes zoster first and chickenpox later in susceptible individuals is an exceedingly rare phenomenon and is considered an unprecedented event that necessitates further exploration.This report presents a case of an 11-year-old girl diagnosed with herpes zoster ophthalmicus (HZO), affecting the ophthalmic division of the right trigeminal nerve. Three days later, she developed chickenpox. The patient’s mother had a documented history of varicella infection during her 32 weeks of gestation. An intriguing aspect of this case is the simultaneous infection of the patient’s younger sister, who resided in the same household and also contracted chickenpox at the same time. Early initiation of antiviral and anticonvulsant therapy effectively mitigated the severity of HZ symptoms, while the varicella manifestations in both siblings remained mild, necessitating only symptomatic management with antipruritic lotion. The zoster lesions required approximately six weeks for complete resolution, leaving behind substantial scarring on the forehead, eyelid edema, and scarring alopecia at the affected site.